A uniaxial constitutive model for NiTi shape memory alloy bars considering the effect of residual strain. (May 2019) - Li, Canjun; Zhou, Zhen; Zhu, Yazhi
Super-elastic shape memory alloys are widely used in structural engineering fields due to their encouraging super-elasticity and energy dissipation capability. Large-size shape memory alloy bars often present significant residual strains after unloading, which emphasizes the necessity of developing a residual strain effect–coupled constitutive model to predict well the performance of shape memory alloy–based structures. First, this article experimentally studies the hysteretic behavior of NiTi shape memory alloy bars under quasi-static loading conditions and investigates the effects of cyclic numbers and strain amplitudes on residual strain. Second, a concept of cumulative transformation strain is preliminarily introduced into a phenomenological Lagoudas model. A uniaxial constitutive model for shape memory alloy bars including the residual strain is proposed. By using OpenSees platform, numerical simulations of shape memory alloy bars are conducted—the results of which indicate that the proposed model can accurately capture the hysteretic behavior of shape memory alloys. The predicted residual strains show a good agreement to experimental results, which demonstrates the desirable efficiency of the proposed model.